Saramago's Philosophical Heritage (Springer International Publishing, 2018)
The past decades have seen a growing "philosophical" interest in a number of authors, but strangely enough Saramago's oeuvre has been left somewhat aside. This volume aims at filling this gap by providing a diverse range of philosophical perspectives and expositions on Saramago's work. The chapters explore some possible issues arising from his works: from his use of Plato's allegory of the cave to his re-readings of Biblical stories; from his critique and "reinvention" of philosophy of history to his allegorical exploration of alternative histories; from his humorous approach to our being-towards-death to the revolutionary political charge of his fiction. The essays here confront Saramago's fiction with concepts, theories, and suggestions belonging to various philosophical traditions and philosophers including Plato, Pascal, Kierkegaard, Freud, Benjamin, Heidegger, Lacan, Foucault, Patočka, Derrida, Agamben, and Žižek.